Reproductive Morbidity Profile Among Ever Married Women (15-44) Years of Rural Etawah District, Uttar Pradesh: A Cross-Sectional Study - Rani, Vidya; Dixit, Anand M; Kumar, Sandip; Singh, Naresh P; Jain, Pankaj Kumar; Peeyush, Kariwal (National Journal of Community Medicine, 2016)
Introduction: Reproductive Tract Infections (RTIs) including Sexually Transmitted infections (STIs) are silent epidemics and are recognized as public health problem and rank second as the cause of healthy life lost among women of reproductive age. Considering the importance we planned study in our area with following Objective: To know the prevalence of reproductive morbidity among married women (15-44 Yrs) in rural area of Etawah district and to find out associated factors. Methods: A cross sectional study was done on 370 married women of rural area of Etawah district. Multi stage random sampling was adopted. A structured questionnaire was used to assess the morbidity and correlated factors. Chi -square test used for analysis. Morbidity was based on symptoms. Results: Among 370 married women 173(46.76 %) women had one or more symptoms of reproductive morbidity. Per woman average symptoms of reproductive morbidity was found to be 1.6.Most common symptoms of reproductive morbidity were vaginal discharge (28.92%), lower abdominal pain (21.08%) and menstrual problem (20.27%). Conclusion: Study reveals that prevalence of reproductive morbidity is very common among women of reproductive age group.